2007
DOI: 10.1093/nar/gkl1099
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the RepB initiator protein of plasmid pMV158 and two distant DNA regions within the origin of replication

Abstract: Plasmids replicating by the rolling circle mode usually possess a single site for binding of the initiator protein at the origin of replication. The origin of pMV158 is different in that it possesses two distant binding regions for the initiator RepB. One region was located close to the site where RepB introduces the replication-initiating nick, within the nic locus; the other, the bind locus, is 84 bp downstream from the nick site. Binding of RepB to the bind locus was of higher affinity and stability than to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…RepB specifically recognizes its cognate origin by binding to the bind locus of the pMV158 dso (del Solar et al , 1993). The bind locus consists of a triple 11‐bp direct repeat and can be assumed to be a B‐DNA duplex that severely bends on binding of RepB (Ruiz‐Masó et al , 2007). Our studies show that RepB 6 binds to a single dsDNA containing the triple direct repeat (Figure 5B and C) and that RepB 1 , RepB 2 and RepB 6 are the predominant species in vivo (Supplementary Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…RepB specifically recognizes its cognate origin by binding to the bind locus of the pMV158 dso (del Solar et al , 1993). The bind locus consists of a triple 11‐bp direct repeat and can be assumed to be a B‐DNA duplex that severely bends on binding of RepB (Ruiz‐Masó et al , 2007). Our studies show that RepB 6 binds to a single dsDNA containing the triple direct repeat (Figure 5B and C) and that RepB 1 , RepB 2 and RepB 6 are the predominant species in vivo (Supplementary Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins having a Rep-3 domain also perform strand-transfer reactions generally seen during rolling circle (RC) replication (Moscoso et al 1995; Ruiz-Maso et al 2007). RC replication is also seen during horizontal transfer of indigenous plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…This seems to be the case in pMV158, where the extrusion frequency of the cruciform involving IR-I is very low at the growth temperature of the plasmid host (37°C) (69). In vitro footprinting experiments performed with supercoiled pMV158 DNA showed that binding of RepB to the nic locus promotes the extrusion of the IR-I cruciform, which in turn indicates that initiation of replication would take place only when specific binding of RepB occurs (64). Genetic analysis of the pC194 dso pointed to the existence of a hairpin located downstream of the nick site (70) that was shown to be important for replication of the plasmid (71).…”
Section: The Double-strand Originmentioning
confidence: 97%
“…Interestingly, the existence of distant DRs has not been elucidated in some plasmids of this subfamily (unpublished observation). The role of the different regions of the pMV158-dso in the interaction with the plasmid-encoded RepB initiator protein has been addressed in a systematic study (35,(61)(62)(63)(64). RepB binds with high affinity to the bind locus, which is made up of three 11-bp tandem DRs located 84 bp downstream from the nick site.…”
Section: The Double-strand Originmentioning
confidence: 99%
See 1 more Smart Citation